GAMBARAN PENGETAHUAN PEDAGANG DALAM PENGGUNAAN FORMALIN PADA IKAN ASIN DI PASAR TRADISIONAL KEDUNGPRAHU - Wulandari, Windi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Introduction: Formalin is a type of food additive that is not permitted, the use of formalin as a food additive is increasingly prevalent among the community, especially in salted fish. Ingestion of formalin in small amounts is harmful to the body because after contact it can damage body cells. The Kedungprahu traditional market has never been inspected for food safety, especially formalin. The purpose of this study was to describe the knowledge of traders in the use of formalin in salted fish in the Kedungprahu traditional market. Methods: This type of research is descriptive using a qualitative analysis approach. The population in this study were 5 salted fish traders, the samples were 5 traders and 14 salted fish, formalin examination of salted fish was carried out qualitatively with the colorimetric method using "Test Kit". Results: The level of knowledge of salted fish traders in the Kedungprahu traditional market is 20% less and the salted fish sold there are 2 types of salted fish identified as positive for formalin. Conclusion: There are still salted fish traders in the Kedungprahu traditional market who do not know the characteristics of salted fish that contain formalin, therefore it is necessary to increase the knowledge of traders regarding the dangers of using formalin in food.Keywords: Knowledge, Formalin, Salted fish